Aix Map Task corpus: The French multimodal corpus of task-oriented dialogue - Gorisch, Jan; Astésano, Corine; Gurman Bard, Ellen; Bigi, Brigitte; Prévot, Laurent (CCSD, 2014)
International audience This paper introduces the Aix Map Task corpus, a corpus of audio and video recordings of task-oriented dialogues. It was modelled afterthe original HCRC Map Task corpus. Lexical material was designed for the analysis of speech and prosody, as described in (Astésanoet al., 2007). The design of the lexical material, the protocol and some basic quantitative features of the existing corpus are presented.The corpus was collected under two communicative conditions, one audio-only condition and one face-to-face condition. The recordingstook place in a studio and a sound attenuated booth respectively, with head-set microphones (and in the face-to-face condition with twovideo cameras). The recordings have been segmented into Inter-Pausal-Units and transcribed using transcription conventions containingactual productions and canonical forms of what was said. It is made publicly available online.